Sleep quality and creativity in Chinese college student during the COVID-19 pandemic: The mediating role of executive function - Guo, Botang; Song, Yue; Zhao, Lu; Cheng, Xinhui; Ma, Hanze; Qiu, Xiaohui; Yang, Xiuxian; Qiao, Zhengxue; Zhao, Erying; Bu, Tianyi; Yang, Jiarun; Mishra, Rupam; et al. (Frontiers in Public Health, 2022)
Background： COVID-19 has brought many changes to adolescents' interpersonal relationships, life attitudes, and mental health during the past three years. However, previous studies mostly focused on negative problems, and few studies observed the situation of teenagers from the perspective of positive psychology. Therefore, this study attempts to explore the creativity level of Chinese college students during the COVID-19 epidemic, explore the relationship between sleep quality and creativity, and verify the mediating role of executive function. Method： A cross-sectional study was conducted in six colleges in Heilongjiang in China using a sample of 4258 college students recruited by stratified cluster sampling. Data were collected through an online survey. A mediation model was constructed, and an SPSS PROCESS macro was used to analyze the data. Results： The creativity level of Chinese college students was medium during the COVID-19 epidemic. The correlation analyses showed that sleep quality directly affected college students' creativity. In addition, the mediation model revealed that executive function partially mediated the link between sleep quality and creativity of college students. Executive function accounted for 48.6% of the variance in college students' creativity. Conclusions： School administrators should improve students' sleep quality through reasonable methods and strengthen sleep education. At the same time, pay attention to the training of executive function in the process of curriculum design and assessment. This helps to improve students' creativity level, to help students overcome the negative emotional impact of the COVID-19.